Periodismo independiente en plataformas digitales - Martínez Gómez, Bella Cristina (2019)
The present investigation covers the development that has been generated in the function of the construction of independent digital information offers, within the national context, the specific form in the city of Guayaquil, the main objective is the function of these independent proposals, and their transcendence Within the digital culture and the technological information boom, the methodological structure is the dual or mixed. Approach, the exploratory system, the descriptive method and the correlates of the problematic needs presented by the object of the study, the preliminary results through the instruments of collection provided the sustenance and necessary contribution for the development and projection of the present theme……….